Preservation of Web-Animation in a Post-Flash Era - Nolan, Eil´ıs (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
At the beginning of 2021, Adobe ended support for Flash Player. The software had been a popular mode of accessing and displaying web-based multimedia content for decades, and its discontinuation has led to a shift in the way amateur and short-form animation can be hosted online. Flash allowed amateur creatives to share animated videos, playable video games, and other multimedia content with audiences over the web. After the announcement that Adobe would no longer be supporting the software, websites and creatives alike who relied on Flash turned to alternative means of disseminating animated works. In the absence of this software, creators and publishers alike have turned to alternative solutions, such as integrating new third-party software, or converting the media to embedded video– without support for interactive elements. Some Flash animations have been taken offline altogether, or have become lost media. The impact of this discontinuation is wide and varied. This paper aims to focus on the impact it has had on the largest web-based visual narrative to date: Andrew Hussie’s cult-classic, multimedia comic Homestuck. During the webcomic’s seven year run, Homestuck amassed over 8000 pages, with a sizable percentage containing Flash animation. The purpose of this case study therefore is to discuss the solutions brought forward by VIZ Media, who had acquired the publishing rights to the comic in 2018, and by volunteer archivists to preserve the original medium of the comic. In using Homestuck as a case study, where multiple forms of preservation and archiving have been attempted, preliminary hypotheses about the effect that Flash Player’s discontinuation has had on amateur web animation can be drawn.